Trade and cooperation opportunities for the MERCOSUR countries in the livestock sector and beef meat in Indonesia - Sterzer, Sebastian; Azizah, Siti (Faculty of Animal Science, Universitas Brawijaya, 2021)
Indonesia is the largest economy in the Southeast Asia region, with the largest population in that region as well. Therefore, each productive and industrial sector that helps the growth and development of the country and its population gets attraction. The livestock sector can be a good example of the above. In this sense, the countries that make up the Southern Common Market (MERCOSUR), that is, Argentina, Brazil, Paraguay, and Uruguay (Venezuela is suspended) can contribute to develop the livestock sector in Indonesia, looking for further cooperation and business opportunities that can also help to improve the well-being of Indonesians. The objective in this article will be to make a brief approach to the Indonesian livestock sector in general and the beef market, to understand how the MERCOSUR countries could contribute to the development of that. The results of the analysis indicate that Indonesia should develop its livestock sector using best practices that contribute to sustainable development, with support from the public sector. The use of new technologies could contribute to the improvement of the sector, and bovine genetics can contribute to a greater and better supply. It is concluded that the MERCOSUR countries have opportunities to contribute to the growth and development of the livestock sector in Indonesia, through the signing of relevant legal agreements both at the bilateral level and, in the case of MERCOSUR, acting as a bloc.